Unusual external branch of the superior laryngeal nerve: a case report - Pulakunta, Thejodhar (Cases Network Ltd, 2009)
INTRODUCTION: The knowledge of the branching pattern of external branch of the superior laryngeal nerve and its relationship with the superior thyroid artery is the key point for identifying the external branch of the superior laryngeal nerve during surgeries of the neck. CASE PRESENTATION: During routine dissection of the left head and neck region of a 50 years old female cadaver, we observed a variation of the external branch of the superior laryngeal nerve around the superior thyroid artery. The external branch of the superior laryngeal nerve has presented one medial and three lateral branches. The medial branch was running on the surface of the inferior constrictor and pierced it; where as the lateral three branches are located laterally to the superior thyroid artery. The medial two lateral branches were piercing the substance of the thyroid gland, where as the lateral most branch was communicating with the left sympathetic chain. CONCLUSION: It is very important that surgeons carefully dissect the region of the superior pole of the thyroid gland to expose the abnormal branching pattern of external branch of the superior laryngeal nerve prior to ligation of individual thyroid vessels.